Kingdom of Swaziland : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Setting: Swaziland has gradually recovered from the fiscal crisis of 2010-11, buoyed by the improved revenues from the Southern African Customs Union (SACU). Growth modestly recovered, and international reserves rebounded. Swaziland's challenges, however, remain significant, in view of its high vulnerability to exogenous shocks and its sluggish growth performance, while facing significant social and development challenges with high unemployment and the prevalence of HIV/AIDS. Swaziland now stands at a critical juncture to strengthen its resilience to exogenous shocks, address its weak growth performance, and meet critical social and development needs. Outlook and risks: Under the status-quo policies, the outlook is for continued sluggish growth and increasing fiscal and external imbalances, reflecting low private investment, elevated government spending, and prospective decline in SACU revenues. Risks are associated with the high volatility of the SACU revenues, possible negative spillovers from South Africa (including higher policy rate and lower growth), and uncertain prospects for preferential trade agreements with the U.S. and EU. Strengthening Resilience to Shocks: Over the medium term, international reserves should be targeted at five to seven months of imports, and public debt be kept below 30 percent of GDP. This calls for a prudent fiscal policy stance, with fiscal deficit below 2 percent of GDP. Raising growth: It is essential to enhance the efficiency of the public sector and promote private sector-led growth through structural reforms including improving business climate and accelerating land reforms. Maintaining financial stability: Financial soundness indicators are generally strong. The strong growth of the nonbank financial sector in recent years calls for strengthening of supervision and regulation for the sector. Past advice: There is broad agreement between the Fund and the authorities on macroeconomic policy and structural reform priorities. With the authorities' fiscal consolidation efforts and the improved SACU revenues, fiscal and external sustainability is being restored, consistent with staff's advice. However, progress on structural reforms-including re-launching the privatization process, improving access to modern finance and improving the business climate-has been modest.